Interrelations of Epicardial Fat Volume, Left Ventricular T1-Relaxation Times and Myocardial Strain in Hypertensive Patients: A Cardiac Magnetic Resonance Study. Issue 3 (May 2017) - Homsi, Rami; Kuetting, Daniel; Sprinkart, Alois; Steinfeld, Nina; Meier-Schroers, Michael; Luetkens, Julian; Nadal, Jennifer; Dabir, Darius; Fischer, Stefan; Gieseke, Juergen; Schild, Hans; Thomas, Daniel
Abstract : Purpose: This cardiac magnetic resonance study was performed to assess myocardial fibrosis by evaluating T1-relaxation time (T1), to measure left ventricular (LV) strain, and to determine epicardial fat volume (EFV) in hypertensive patients with no history of cardiovascular (CV) events and to relate the results to the presence of coronary atherosclerotic artery disease (CAD) in these patients. Materials and Methods: A total of 123 subjects were examined at 1.5 T. Of them, 98 were hypertensive patients (58 men; mean age, 62.9±10.7 y; body mass index, 29.0±5.6 kg/m 2 ) and 25 were controls without CV risk factors or disease (13 men; 60.1±10.7 y; 28.1±5.4 kg/m 2 ). All patients had a well-treated blood pressure. In the hypertensive group, 56 patients had no CAD, whereas 42 patients had CAD. T1 was assessed by a modified Look-Locker inversion recovery sequence. Longitudinal and circumferential peak systolic strain (LS; CS) was determined with dedicated cardiac magnetic resonance software (feature tracking). EFV (normalized to the body surface area) was assessed by a 3D Dixon sequence. Results: T1 (ms) and EFV (mL/m 2 ) were higher and CS and LS (%) were lower in hypertensive patients compared with those in nonhypertensive controls ( P <0.05), independent of the presence of CAD (controls: T1=967.2±16.9, LS=−25.2±4.6, CS=−28.7±5.0, EFV=58.2±21.1; hypertensive patients overall: T1=991.3±45.5, LS=−21.0±4.5, CS=−25.0±5.9, EFV=71.1±25.3; hypertensive patients without CAD: T1=991.6±48.4, LS=−21.0±4.7, CS=−24.6±6.3, EFV=71.3±26.6; hypertensive patients with CAD: T1=986.7±39.2, LS=−21.1±4.3, CS=−25.5±5.4, EFV=70.9±23.6). There were no significant differences between hypertensive patients with and those without CAD and between patients grouped according to the number of vessels affected (0-vessel disease, 1-vessel disease, 2-vessel disease, or 3-vessel disease). Conclusions: Hypertension is associated with signs of myocardial fibrosis and an impaired LV contractility despite a normal LV ejection fraction, as well as with an increased EFV. However, CAD, in the absence of previous pathologies with consecutive myocardial ischemic damage, did not additionally affect these parameters.